Asian crocodile poaching: A review of molecular techniques developed for forensic identification - Ishani Mitra; Soma Roy; Ikramul Haque (Wolters Kluwer Medknow Publications, 2022)
Crocodiles, gharials and alligators (order Crocodilia), are aquatic reptiles that live in the tropics of Asia, America, Africa, and Australia. Asian countries such as India, Indonesia, Malaysia, and tropics of Australia are the stronghold of the family Crocodylidae. Among all 23 crocodile species, nine species occur in Asia and its surroundings, including the only member of Gavialidae and Alligatoridae family. They are "mugger" or "Crocodylus palustris," "saltwater crocodile" or "Crocodylus porosus," "Philippine crocodile" or "Crocodylus mindorensis," "New Guinea crocodile" or "Crocodylus novaeguineae," "Siamese crocodile" or "Crocodylus siamensis," "gharials" or "Gavialis gangeticus," "false gharial" or "Tomistoma schlegelii," and "Chinese alligator" or "Alligator sinensis." All of these species have been encompassed in "Appendix I" and "Appendix II" of the "Convention on International Trade in Endangered Species of Wild Fauna and Flora," which prevents any kind of trade involving crocodilian species. However, it has been observed that these crocodiles are illegally poached and trafficked for their lucrative skin, meats, eggs, snouts, and bones in medicinal and cosmetic industries. Although many molecular biologists have come forward for the conservation of these species, lack of knowledge about the available, fast, and dependable techniques makes it difficult for forensic identification of seized or confiscated. It has been a major problem for the implementation of the "Wildlife Protection Law" on illegal trade. This article focuses on molecular techniques developed till date for the rapid and reliable species identification and conservation study of them.